2016
DOI: 10.1186/s40064-016-2512-y
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-21 plays a critical role in the pathogenesis and severity of type I autoimmune hepatitis

Abstract: Background and aimsRecently, the number of follicular helper T (Tfh) cells expressing interleukin (IL)-21 was found to increase in peripheral blood of human and murine models of autoimmune hepatitis (AIH). IL-21, the most recently discovered member of the type-I cytokine family, exerts various effects on the immune system, including B cell activation, plasma cell differentiation, and immunoglobulin production. We aimed to assess the relationship of serum IL-21 levels in patients with type I AIH with clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
2
25
1
5
Order By: Relevance
“…Similar to our findings, studies from HIV infected patients have shown impaired IL-21 during acute HIV infection when compared to uninfected controls [55] and that this impairment was partially rescued when ART was initiated [55]. Previous published IL-21 levels from the healthy donors were also similar to our IL-21 levels from our non-TB healthy controls cohort [56]. In mouse models, it has been reported that IL-21 signaling has a key role in promoting the protective capacity of T cells.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings, studies from HIV infected patients have shown impaired IL-21 during acute HIV infection when compared to uninfected controls [55] and that this impairment was partially rescued when ART was initiated [55]. Previous published IL-21 levels from the healthy donors were also similar to our IL-21 levels from our non-TB healthy controls cohort [56]. In mouse models, it has been reported that IL-21 signaling has a key role in promoting the protective capacity of T cells.…”
Section: Discussionsupporting
confidence: 91%
“…This population decreases significantly consecutively to prednisolone treatment, with the decrease of serum alanine transferase ( 201 ). Serum levels of IL-21 are higher in patients with AIH than in patients with other liver diseases or healthy volunteers ( 202 , 203 ), correlating with the numbers of cTfh cells. They are associated with the severity of the disease.…”
Section: Hepatological and Gastroenterological Diseasesmentioning
confidence: 95%
“…They are associated with the severity of the disease. Finally, they correlate positively with total serum bilirubin levels and negatively with serum albumin ( 203 ). Data obtained from immunohistochemistry studies and from flow cytometry on extracted cells from liver biopsies of patients with AIH have been also published: frequencies of activated Tfh cells are significantly increased in the liver from patients and positively correlate with their circulating counterparts in blood of patients ( 201 ).…”
Section: Hepatological and Gastroenterological Diseasesmentioning
confidence: 99%
“…The complex interplay of several cytokines, especially proinflammatory and Th17 cytokines, and Treg suppression by IL‐12p40 play a pivotal role in the pathogenesis of AIH. We previously found that serum IL‐21 levels were significantly higher in severe AIH cases compared to nonsevere cases and that serum IL‐21 level correlated positively with TB level and necroinflammatory activity grade . Moreover, a recent study revealed that IL‐21 and IL‐33 are potent regulators of HBV clearance .…”
Section: Discussionmentioning
confidence: 96%
“…We previously found that serum IL-21 levels were significantly higher in severe AIH cases compared to nonsevere cases and that serum IL-21 level correlated positively with TB level and necroinflammatory activity grade. (48) Moreover, a recent study revealed that IL-21 and IL-33 are potent regulators of HBV clearance. (49) This relationship between IL-21 and IL-33 is also expected in the pathogenesis of AIH.…”
Section: Discussionmentioning
confidence: 99%